Longitudinal transactions between personality and occupational roles: A large and heterogeneous study of job beginners, stayers, and changers - Jaap J. A. Denissen; Hannah Ulferts; Oliver Lüdke; Peter Manfred Muck; Denis Gerstorf (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Social norms are central to theoretical accounts of longitudinal person-environment transactions. On the one hand, individuals are thought to select themselves into social roles that fit their personality. On the other hand, it is assumed that individuals' personality is transformed by the socializing pressure of norm demands. These two transactional directions were investigated in a large and eterogeneous 5-year longitudinal subsample of job beginners (n = 640, M age = 21.24), job stayers (n = 4,137, M age = 46.63), and job changers (n= 2,854, M age = 44.68) from the German Socio-Economic Panel. Role demands were coded by both students and labor market experts. To demonstrate transactional effects, cross-lagged structural equation models were estimated. Substantial selection effects were found for both job beginners and job changers. There was also evidence for socialization effects, especially for participants who did not change jobs. Depending on the trait and the subsample that was investigated, selection effects were sometimes corresponsive with socialization effects. Personality role demands were temporally consistent across a four-year period even when individuals changed jobs (heterotypic continuity). This is one of the first empirical demonstrations of the transactional processes that lead to the formation of social niches.
Keywords: 330; personality development; person-environment transactions; job characteristics; occupational roles; longitudinal study